If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7ab * a = 36ab Multiply ab * a 7a2b = 36ab Solving 7a2b = 36ab Solving for variable 'a'. Reorder the terms: -36ab + 7a2b = 36ab + -36ab Combine like terms: 36ab + -36ab = 0 -36ab + 7a2b = 0 Factor out the Greatest Common Factor (GCF), 'ab'. ab(-36 + 7a) = 0Subproblem 1
Set the factor 'ab' equal to zero and attempt to solve: Simplifying ab = 0 Solving ab = 0 Move all terms containing a to the left, all other terms to the right. Simplifying ab = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-36 + 7a)' equal to zero and attempt to solve: Simplifying -36 + 7a = 0 Solving -36 + 7a = 0 Move all terms containing a to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 7a = 0 + 36 Combine like terms: -36 + 36 = 0 0 + 7a = 0 + 36 7a = 0 + 36 Combine like terms: 0 + 36 = 36 7a = 36 Divide each side by '7'. a = 5.142857143 Simplifying a = 5.142857143Solution
a = {5.142857143}
| 2(x-1)-5(x+2)=10 | | 3(3+x)=7(2-X)+5 | | (2x+7)(5x-2)=0 | | (2x-1)*(-x^2+2x-3)=3 | | x^5=1.333 | | 0=4x^2-4x-3-y | | 7-2(10x+1)=25 | | 8x+2+3x+6=x+12 | | 7x+5+x-3+x=5 | | 3x-2(x+3)=9 | | 12=20x-18 | | 3(5x+10)+10=6x-(x+10) | | 12/30n=-38 | | 13x+11y+6z=42 | | 3x^3+x^2+75x+25=0 | | x^5-6*x^4+5*x^3=0 | | x^3-5*x^2+9*x+13=0 | | 160=5x+10x+4 | | 4(3x+1)=32 | | -20=-x-6x | | 5x+10y=350 | | (6y+5)-3+5y=5 | | x^2-(2b-1)x+(b^2-b-20)x=0 | | 42x=700 | | x^2+40x-48000=0 | | x^2+20x-48000=0 | | 3x+85=49 | | 4*x^2-2*x-12=0 | | cos(x)=-0.2 | | x(5a-12-a^2)=3-2a | | (x-3)(6x-5)=0 | | n+30= |